Fans and Followers: Marketing Charisma, Making Religious Celebrity in Ghana - Witte, Marleen de (Australian religion studies review, 2011)
Presenting a case study of the Ghanaian charismatic-Pentecostal celebrity-pastor Mensa Otabil, this article explores processes of marketing and mass mediating charisma in the making of religious celebrity. In order to grasp the convincing force of this Man of God', it moves beyond classical Weberian and theological understandings of charisma by looking at styling, marketing, and branding strategies. Thus analyzing the making of' reli¬gious celebrity in the broader context of Ghana's religious arena, the secular celebrity scene, and global charismatic Christianity, it argues that while part of the global charismatic movement with its jet set leaders and high tech styling, Ghanaian charismatic celebrities are also rooted in traditional modes of religious celebrity'. Otabil's charisma—or his fans' and followers' perception of his supernatural giftedness—derives largely from his being (crafted as) a national and international star. Despite clear similarities to secular' stardom, the specificity of religious celebrity lies, in the case of Ghanaian pastors, in how the contagious aura of celebrity connects to traditional beliefs in the power of religious specialists. The religious authority of African Men of God' such as Otabil thrives, I argue, on an embodied fusion of the mass mediated and marketed charisma of modern celebrity and the perceived power of traditional shrine priests as intermediaries between the human and the spirit world. The magical aura of celebrity at work in the transmission of Holy Spirit power through the Man of God' to his followers is fragile though, perpetually challenged by the possible visibility of the making of' threatening to undermine Otabil's authenticity.